2020
DOI: 10.1111/jfd.13139
|View full text |Cite
|
Sign up to set email alerts
|

The composition of the microbial community associated with Macrobrachium rosenbergii zoeae varies throughout larval development

Abstract: The giant river prawn, Macrobrachium rosenbergii, is an economically important freshwater prawn. The cultivation of zoea larvae is crucial for the success of the M. rosenbergii industry. In this study, we surveyed the microbial community diversity and structure associated with M. rosenbergii zoeae at different stages of larval development. Samples of zoea larvae from different developmental stages were collected and subjected to high‐throughput DNA sequencing. Firmicutes, Proteobacteria, Bacteroidetes and Acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 43 publications
1
1
0
Order By: Relevance
“…Specifically, Proteobacteria was the most dominant phyla in all the investigated samples. These results are consistent with the previous observation in the red crayfish ( P. clarkii ) [ 44 ] and other Crustaceans , such as the Pacific white shrimp ( L. vannamei ) [ 16 , 32 ], black tiger shrimp ( P. monodon ) [ 34 ], cherry shrimp ( N. denticulata ) [ 31 ], giant freshwater prawn ( M. rosenbergii ) [ 35 ], and Norway lobster ( N. norvegicus ) [ 30 ]. The Proteobacteria are dominant in aquatic invertebrate gut microbiotas of Crustacea and have high diversity in terms of physiology, morphology, and genetics [ 45 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Specifically, Proteobacteria was the most dominant phyla in all the investigated samples. These results are consistent with the previous observation in the red crayfish ( P. clarkii ) [ 44 ] and other Crustaceans , such as the Pacific white shrimp ( L. vannamei ) [ 16 , 32 ], black tiger shrimp ( P. monodon ) [ 34 ], cherry shrimp ( N. denticulata ) [ 31 ], giant freshwater prawn ( M. rosenbergii ) [ 35 ], and Norway lobster ( N. norvegicus ) [ 30 ]. The Proteobacteria are dominant in aquatic invertebrate gut microbiotas of Crustacea and have high diversity in terms of physiology, morphology, and genetics [ 45 ].…”
Section: Discussionsupporting
confidence: 92%
“…This accounts for more than half of crayfish output in the country and is a major source of income for local farmers [ 28 ]. Previous studies have applied the next-generation sequencing to describe the gut bacterial communities in Decapods including the European lobster ( Homarus gammarus ) [ 29 ], Norway lobster ( Nephrops norvegicus ) [ 30 ], cherry shrimp ( Neocaridina denticulate ) [ 31 ], Pacific white shrimp ( L. vannamei ) [ 16 , 32 , 33 ], black tiger shrimp ( Penaeus monodon ) [ 34 ] and giant freshwater prawn ( Macrobrachium rosenbergii ) [ 35 ]. However, there is limited information on gut bacterial communities of red swamp crayfish ( P. clarkii ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, a shift in diet from yolk or redworms as a juvenile to shrimp or crab as an adult comes with a change in the composition of the intestinal microbial community in the Chinese giant salamander (Andrias davidianus) [22]. A previous study found that Firmicutes, Proteobacteria, Bacteroidetes and Actinobacteria were the dominant phyla in zoeae, and varied throughout the larval development of freshwater prawns (Macrobrachium rosenbergii) [8]. In our study, only the three phyla Firmicutes, Proteobacteria and Actinobacteria were dominant in one-month-old prawns, and the relative abundance of Firmicutes decreased, while that of Proteobacteria increased with the growth of freshwater prawns under pond culture conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the structure and composition of the intestinal microbiota are involved in host immune adaptations and health [4], such as Campylobacter abundance in the gut of chicken (0 to 7 D of age), which is associated with increased expression of the immune gene beta-defensin. The intestinal microbiota has been found to be involved in the growth and nutrient digestion of the host in humans and aquatic animals [5][6][7]; it is also highly associated with the development of the host [8]. For example, the intestinal microbial diversity of Macrobrachium rosenbergii decreased significantly with development in the zoeae larva stage from zoeae to postlarvae, but the dominant phyla of the microbial community were the same.…”
Section: Introductionmentioning
confidence: 99%